A Literature Review of Non-Performing Loan - Ardhi Khairi; Bahri Bahri; Bhenu Artha (Profesional Muda Cendekia Publishing, 2021)
Lending is the primary business of retail banking and non-performing loans (NPLs) have been the focus of attention in recent years. In the wake of the 2008–2010 financial crisis, non-performing loans (NPLs) had increased everywhere, but in some countries they had reached unprecedented heights. Several banks have experienced a particularly challenging period over recent years and the Great Financial Crisis has highlighted the weakness of the banking system and the need to further investigate banks’ asset quality and transparency from both a regulatory and an accounting perspective, which pressure by different institutions for a more accurate assessment of loan portfolios led to the general need for higher provisioning in a period characterised by extremely low interest rates and low bank profitability. The objective of this research is to determine the factors associated with non-performing loans. We presented a literature study using systematic literature review of relevant publications and as a result of this process, we included 21 articles and then examined the bibliographical references to check the validity of the inquiry and to avoid any potential omissions. We identified several variables that affect NPLs and those that are influenced by NPLs. We found no variables that associate with policies, and strongly suggest research for variables that associate with policies.